Saprobic Index and Composition of Phytoplankton in the Sungai Jang, Tanjungpinang, Indonesia - Tengku Said Razai; Thamrin Thamrin; Nofrizal Nofrizal; Viktor Amrivo; Ramses Ramses; Yusni Ikhwan Siregar; Imam Pangestiansyah Putra; Rika Kurniawan (Riau University, 2020)
Environmental pollution that occurs in Tanjungpinang City, cannot be separated from the pollution of the aquatic ecosystem. Water pollution is caused by the presence of waste from residential activities, shops, industry, and other activities that produce waste. Likewise, what happens in the waters of the Sungai Jang, the activities of settlements, shops, industry can cause water pollution in this area, so a study is needed to see the extent of environmental pollution. The indicator used to determine the level of water pollution is by looking at the saprobity index through the phytoplankton community. This research was conducted by dividing the research stations based on differences in activity, namely; station 1 (settlements), station 2 (mangroves), station 3 (shops, industry), station 4 (reclamation). The results showed that the composition of the phytoplankton species found in the waters of the Sungai Jang, Tanjungpinang consisted of 17 species which were classified into 5 divisions. Diatomae types have the most number of species among other divisions, and the most dominating. The dominance of phytoplankton from the class Bacillariophyceae (Diatomae) cannot be separated from the role of nutrients in the water. The average saprobic index value of -0.39 is classified as Moderately Polluted (Meso Saprobik). Pollution that occurs is a result of organic waste from existing activities, causing an increase in nutrients. From the results of measurements in the field, the nutrient content (nitrate and phosphate) in the waters of the Sungai Jang had exceeded the quality standard.